2022
DOI: 10.1021/acsmaterialslett.2c00371
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrafast and Stable High-Entropy Metallic Glass Electrode for Alkaline Hydrogen Evolution Reaction

Abstract: A new type of high-entropy alloy with a composition of Pt 25 Pd 25 Ni 25 P 25 (at.%) and an amorphous structure, referred to as a high-entropy metallic glass (HEMG), was developed by a scalable metallurgical technique for efficient hydrogen evolution reaction (HER). The achieved overpotential was as low as 19.8 mV at a current density of 10 mA cm −2 while maintaining an ultrareliable performance for 60 h in 1.0 M KOH solution, exhibiting 5-and 10-times higher performance than those of traditional Pt 60 Ni 15 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…6c ). Jia et al 103 found that alloying P with Pt, Pd, and Ni with equal atomic ratios would lead to an amorphous HEA. Pt 25 Pd 25 Ni 25 P 25 exhibits 5- and 10-fold higher activity for the HER in alkaline solutions when compared with ternary Pt 60 Ni 15 P 25 and Pd 40 Ni 40 P 20 amorphous alloys, respectively, and surpasses the performance of Pt/C ( Fig.…”
Section: Composition Regulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…6c ). Jia et al 103 found that alloying P with Pt, Pd, and Ni with equal atomic ratios would lead to an amorphous HEA. Pt 25 Pd 25 Ni 25 P 25 exhibits 5- and 10-fold higher activity for the HER in alkaline solutions when compared with ternary Pt 60 Ni 15 P 25 and Pd 40 Ni 40 P 20 amorphous alloys, respectively, and surpasses the performance of Pt/C ( Fig.…”
Section: Composition Regulationsmentioning
confidence: 99%
“…DFT calculations reveal that the high CO 2 reduction is due to multi-site catalysis where the atomic-scale disorder optimizes the rate-limiting step (CO desorption) by facilitating isolated edge sites with weak CO binding (Fig.6c). Jia et al103 found that alloying P with Pt, Pd, and Ni with equal atomic ratios would lead to amorphous HEA. The Pt 25 Pd 25 Ni 25 P 25 exhibits 5 and 10-fold higher activity for HER in alkaline solutions when compared with ternary Pt 60 Ni 15 P 25 and Pd 40 Ni 40 P 20 amorphous alloy, respectively, and surpasses performance of Pt/C (Fig.…”
mentioning
confidence: 99%
“…Unlike crystalline NM-HEA with well-dened atomic structure, NM-HEMG with high homogeneity, shortterm and long-term disordered atomic structure 24 was found to possess a reorganized surface, contributing to more electrochemical active surface area and enhanced intrinsic activity. [25][26][27] For example, Jia et al showed that Pt 25 Pd 25 Ni 25 P 25 HEMG exhibited the overpotential of 19.8 mV at a current density of 10 mA cm −2 in KOH solution, 28 surpassing that of other Pt-and Pd-based catalysts. It was demonstrated that the outstanding HER performance was due to the combination of synergistic effect and unsaturated atomic conguration, which optimized the adsorption and desorption of hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen, featuring the high enthalpy of combustion and zero emission, is considered one of the most promising energy carriers. Electrocatalytic water hydrolysis offers a sustainable strategy for high-purity hydrogen generation powered by green electricity from intermittent renewable energy, such as wind, solar, and tide energy. In an acidic medium, water splitting generally needs expensive proton exchange membrane systems and platinum group metal-based electrocatalysts for hydrogen production. , The alkaline water electrolysis setup presents an attractive alternative with superb durability, corrosion resistance, and operationality at low cost. , However, even for platinum group metals, the benchmark hydrogen evolution reaction (HER) electrocatalyst exhibits 2–3 orders of magnitude lower activity in alkaline electrolytes as compared to acidic media. Unlike the abundant proton (H + /H 3 O + ) supply in acid electrolytes, the origin of H + or adsorbed hydrogen (H ad ) in alkaline media is more complicated. , The catalytic elementary steps in alkaline conditions involve the adsorption of H 2 O, followed by a dissociation process (Volmer step: H 2 O + e – → H ad + OH – ) to generate adsorbed hydrogen (H ad ) and hydroxyl (OH ad ). The OH ad will be released as OH – to refresh the catalyst surface, and the H ad intermediate will undergo either the Heyrovsky step (H 2 O + H ad + e – → H 2 + OH – ) or the Tafel step (H ad + H ad → H 2 ) for H 2 generation. , However, the high intrinsic activation barrier of water dissociation hinders the efficient HER operation . The ability of catalytic active sites to dissociate water is closely related to their adsorption energies with H ad and OH ad .…”
Section: Introductionmentioning
confidence: 99%